Teaching sustainability/teaching sustainably - Bartels, Kirsten Allen 1968-; Parker, Kelly A. 1963- (Stylus Publishing, LLC, 2012)
Over the coming decades, every academic discipline will have to respond to the paradigm of more sustainable life practices because students will be living in a world challenged by competition for resources and climate change, and will demand that every academic discipline demonstrate substantial and corresponding relevance. This book takes as its point of departure that integrating a component of sustainability into a discipline-specific course arises from an educator asking a simple question: in the coming decades, as humanity faces unprecedented challenges, what can my discipline or area of.